Freedom in the High Seas - A Agus Tjahjono; Noor Sulistiyono; Dahlia Dewi A (IWJ : Inland Waterways Journal, 2020)
This study is to determine how the implementation of the use of forms of freedom in the high seas according to the 1982 Convention on the Law of the Sea (UNCLOS 1982) and how the exceptions to freedom in the high seas according to the 1982 Convention on the Law of the Sea (UNCLOS 1982) The research method used in this research is to use normative legal research methods and it can be concluded that: 1. Regulations regarding the high seas are contained in Part VII Article 86 to Article 120 of the 1982 Convention on the Law of the Sea. Each country is granted both a coastal country and a non-coastal state given the right and freedom to utilize the high seas. The freedom of the state on the high seas is freedom in accordance with Article 87, namely freedom of navigation, flight, installing submarine cables and pipes, freedom to build artificial islands and other installations, freedom to catch fish, and freedom to carry out scientific research. Every country can take advantage of every given freedom, but every country is obliged to protect and utilize the high seas for peaceful purposes for the survival of humans. 2. In addition to providing freedom to use the high seas, the 1982 Law of the Sea Convention provides exceptions to these freedoms. Where every country is free to take advantage of the high seas but is not allowed to commit illegal acts or violate laws, both national and international laws, which in its application are often violated by countries in the world. There are several exceptions to the freedom of the high seas, such as the prohibition on slavery, piracy, trafficking of narcotic drugs and psychotropic substances, instant chase, illegal broadcasting, and pollution of the marine environment. Therefore, every country, both coastal and non-coastal countries, is obliged to cooperate in eradicating all forms of abuse of freedom on the high seas.